2006
DOI: 10.1080/16513860500534543
|View full text |Cite
|
Sign up to set email alerts
|

Survey of care pathway for auditory processing disorder

Abstract: In October 2003, the British Society of Audiology instigated the development of a Special Interest Group to study auditory processing disorder (APD) in the UK, and a steering committee was appointed. There is limited epidemiological information on APD, mainly because there is no general agreement on diagnostic markers. This is exacerbated by the potential overlap between the symptomatology of APD and other developmental conditions that impact on differential diagnosis. Children are referred for and receive cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
45
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 6 publications
7
45
2
Order By: Relevance
“…It would also be useful to ascertain if and how (C)APD is currently taught in relevant undergraduate or postgraduate education programs. The participants in the current study reported that they were frustrated about lack of knowledge and training in this area and they were attempting to address this gap through self-directed reading, attendance at training events, and discussing (C)APD with other professionals.With regard to screening and diagnostic services, the findings of this study are similar to Hind (2006) in that the majority of participants neither screen nor diagnose (C)APD. In this study, only 3% of the participants reported that they diagnosed (C)APD and all were SLTs (n = 6).…”
supporting
confidence: 70%
See 3 more Smart Citations
“…It would also be useful to ascertain if and how (C)APD is currently taught in relevant undergraduate or postgraduate education programs. The participants in the current study reported that they were frustrated about lack of knowledge and training in this area and they were attempting to address this gap through self-directed reading, attendance at training events, and discussing (C)APD with other professionals.With regard to screening and diagnostic services, the findings of this study are similar to Hind (2006) in that the majority of participants neither screen nor diagnose (C)APD. In this study, only 3% of the participants reported that they diagnosed (C)APD and all were SLTs (n = 6).…”
supporting
confidence: 70%
“…More than 50% of the respondents rated themselves as being not very well informed about this condition. Of interest, Hind (2006) found that a minimal number of the respondents who reported that they diagnosed APD considered they were very well informed about the condition.Service provision for children with speech, language, communication, hearing and listening needs differs from country to country (e.g., depending on the entry-level qualifications of professionals, governmental funding, structure and organization of services, and population size). The professionals who would be involved in the management of children with (C)APD in Ireland are speech and language therapists, audiological scientists and educational psychologists.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(BSA 2011). Explicitly referring to "nonspeech sounds" emphasizes the difference to linguistic processing (Hind 2006). The BSA further points out "… poor perception of speech alone is not sufficient evidence of APD."…”
Section: Children With Auditory Processing Disordersmentioning
confidence: 99%